Social Impacts Of Bridge Construction Projects - Nabila, Nabila; Edwar, Edwar (CV. SINAR HOWUHOWU, 2024)
Infrastructure development projects, particularly bridge construction, have significant impacts on the social lives of communities. This study aims to analyze various aspects of the social impacts caused by bridge construction projects in Indonesia, focusing on social, cultural, economic, and environmental changes. The methods used in this research include field surveys, in-depth interviews, and secondary data analysis. The results indicate that while bridge projects can enhance accessibility and create job opportunities, there are negative impacts such as population migration, land-related social conflicts, and changes in community lifestyles. This study suggests the need for better management strategies and community involvement in the planning and implementation of projects to maximize benefits and minimize negative impacts on the community.